Analysis of Learning Difficulties of Mathematics for Vocational School Students in the 3T Area - Rahim, Abdurrachman; Mangampang, Elsiana Tappi; Swandi, Ahmad; Rahmadhanningsih, Sri; Salim S, Soma (Indonesian Journal of Educational Studies, 2023)
This study aims to describe the mathematics learning difficulties of vocational high school students in the frontier, outermost and disadvantaged (3T) areas, especially in North Maluku Province, West Halmahera Regency. This type of qualitative descriptive research uses the results of questionnaires, observations, and interviews. The population in this study were students of class X TKJ, X Nautika Perkapalan, and X Asisten Keperawatan SMKS Fomarimoi for the academic year 2022/2023 as many as 19 students and 2 teachers. The results showed that the difficulties in learning mathematics for SMK students in 3T areas West Halmahera, were: (1) difficulties in understanding concepts; (2) difficulty in arithmetic operations; (3) difficulty in solving problems; (4) lack of self-awareness to learn mathematics; (5) low motivation to learn mathematics; (6) less able to determine the formula to be used; (7) facilities and infrastructure are still inadequate; (8) the ability of educators is still low; and (9) limited coverage of learning in 3T areas.